Analisis Pendapatan dan Kelayakan Usaha Agroindustri UMKM Kalamai Urang Awak di Muaro Kecamatan Sijunjung Kabupaten Sijunjung - Elma Inesia Situmorang Lamris simajuntak; Juli Supriyanti; Fildza Arief Syuhada; Roni Jarlis; Andi Alatas (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2026)
This study aims to analyze the income generated by the Kalamai Urang Awak MSME in Nagari Muaro, Sijunjung District, and to assess the business feasibility of its agro-industrial opeRations. The research is driven by the strategic role of agro-industrial MSMEs in the regional economy and the importance of preserving traditional culinary products like kalamai, which possess significant cultural value and economic potential despite challenges in production efficiency and financial management. The method employed is descriptive quantitative, with data collection techniques including observation, interviews, and documentation. Business feasibility is measured using the Revenue-Cost Ratio (R/C Ratio), Break-Even Point (BEP), Payback Period (PP), and Net Present Value (NPV) indicators. The results show that Kalamai Urang Awak generates a monthly net income of Rp59,077,403 from a total revenue of Rp88,920,000, with production costs amounting to Rp29,842,597. The feasibility analysis indicates an R/C Ratio of 2.98, a production BEP of 180 packages per month, and a Payback Period of 1.43 indicating capital recovery within 1 year and 5 months which is well below the actual monthly production of 4,446 packages. Furthermore, the NPV is positive at Rp750,801,087 with a 10% discount rate. Based on these findings, it can be concluded that the Kalamai Urang Awak business is highly profitable and feasible for further opeRation and development as a leading agro-industrial enterprise.